What Skills Pay More? The Changing Demand and Return to Skills for Professional Workers - Cecily Josten; Helen Krause; Grace Lordan; Brian Yeung (Institute of Labor Economics (IZA), 2024)
Technology is disrupting labor markets. We analyze the demand and reward for skills at occupation and state level across two time periods using job postings. First, we use principal components analysis to derive nine skills groups: 'collaborative leader', 'interpersonal & organized', 'big data', 'cloud computing', 'programming', 'machine learning', 'research', 'math' and 'analytical'. Second, we comment on changes in the price and demand for skills over time. Third, we analyze non-linear returns to all skills groups and their interactions. We find that 'collaborative leader' skills become significant over time and that legacy data skills are replaced over time by innovative ones.
Keywords: J10; 330; skills; cognitive skills; soft skills; inclusive leadership; wages; demand for skills